me ajudem!!!!!!!!!!!!!!!!!!!!
Anexos:
![](https://pt-static.z-dn.net/files/d6f/f316faee75e5bfa768f5c532560dd44d.jpg)
Soluções para a tarefa
Respondido por
1
P = (3x - 2)(3x + 2) - x(- x + 1)²
P = 9x² + 6x - 6x - 4 - x( (-x)² - 2.x.1 + 1²)
P = 9x² - 4 - x ( x² - 2x + 1)
P = 9x² - 4 - x³ - 2x² + x
P = - x³ + 7x² + x - 4
P é um polinômio completo e do 3° grau
P = 9x² + 6x - 6x - 4 - x( (-x)² - 2.x.1 + 1²)
P = 9x² - 4 - x ( x² - 2x + 1)
P = 9x² - 4 - x³ - 2x² + x
P = - x³ + 7x² + x - 4
P é um polinômio completo e do 3° grau
raquelcebolinha:
obrigada ajudou muito!
Perguntas interessantes
Matemática,
1 ano atrás
Química,
1 ano atrás
História,
1 ano atrás
Química,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás